Description of Some Aquatic Insect Genera in Greater Zab River Branches, North of Iraq - Khudhur, Shelan; Ahmed Shekha, Yahya (Al-Nahrain Journal of Science, 2021)
Aquatic insects samples were collected from 6 sites along the Greater Zab River in the northern Iraq from Duhok and Erbil governorates over 12 months during September 2016 to August 2017, which belong to seven orders (Ephemeroptera, Plecoptera, Trichoptera, Odonatan, Diptera, Coleoptera, and Megaloptera). Clustering mitochondrial DNA cytochrome c oxidase and 16S rDNA genes, morphological keys, and matches in the Barcode of Life Database, we identified 24 species return to 7 orders and 12 families, as indicated in the results. The reported species were: Ephemeroptera 5 members of the family Heptageniidae (Maccaffertium meririvulanum, Raptoheptagenia cruentata, Ecdyonurus dispar, Anepeorus rusticus,  Stenonema femoratum), 1 Ephemerellidae (Seratella ignita), 1 Arthropleidae (Arthroplea bipunctata), 6 Baetidae (Baetis alpinus, Baetis braaschi, Baetis noa, Baetis harrisoni, Iswaeon anoka, Heterocloeon amplum), 1 member for each of Diptera, Coleoptera, Megaloptera and Odonatan  orders, while Plecoptera 2 members Leuctridae (Leuctra hippopoides, Leuctra inermis) and Tricoptera 4 members 3 Hydropsychidae (Leptonema albovirens, Hydropsyche simulans, Arctopsyche irrorate), 1 Hydroptilidae (Ochrotrichia tenuata).  Most of these recorded species and genera were mentioned for the first time and represent new records in Iraq. Presence and distribution of identified species varied between studied sites, as a result of differences in biogeographical and physical conditions.